Moral distress in the resuscitation of extremely premature infants. (February 2015) - Molloy, Jennifer; Evans, Marilyn; Coughlin, Kevin
Objective: To increase our understanding of moral distress experienced by neonatal registered nurses when directly or indirectly involved in the decision-making process of resuscitating infants who are born extremely premature. Design: A secondary qualitative analysis was conducted on a portion of the data collected from an earlier study which explored the ethical decision-making process among health professionals and parents concerning resuscitation of extremely premature infants. Setting: A regional, tertiary academic referral hospital in Ontario offering a perinatal program. Participants: A total of 15 registered nurses were directly or indirectly involved in the resuscitation of extremely premature infants. Methods: Interview transcripts of nurses from the original study were purposefully selected from the original 42 transcripts of health professionals. Inductive content analysis was conducted to identify themes describing factors and situations contributing to moral distress experienced by nurses regarding resuscitation of extremely premature infants. Ethical considerations: Ethical approval was obtained from the research ethics review board for both the initial study and this secondary data analysis. Results: Five themes, uncertainty, questioning of informed consent, differing perspectives, perceptions of harm and suffering, and being with the family, contribute to the moral distress felt by nurses when exposed to neonatal resuscitation of extremely premature infants. An interesting finding was the nurses' perceived lack of power and influence in the neonatal resuscitation decision-making process. Conclusion: Moral distress continues to be a significant issue for nursing practice, particularly among neonatal nurses. Strategies are needed to help mediate the moral distress experienced by nurses, such as debriefing sessions, effective communication, role clarification, and interprofessional education and collaboration.